Effects of inorganic and organic fertilizers on CO2 and CH4 fluxes from tea plantation soil - Lin, Shan; Zhang, Shangpeng; Shen, Guoting; Shaaban, Muhammad; Ju, Wenliang; Cui, Yongxing; Duan, Chengjiao; Fang, Linchuan (Elementa (Washington, D.C.), 2021)
Agricultural practices such as fertilization considerably influence soil greenhouse gas fluxes. However, the effects of fertilization on greenhouse gases fluxes remain unclear in tea soil when soil nitrogen is low. In the present study, soil CO2 and CH4 fluxes under various fertilization treatments in tea soil were investigated during a 50-day period. The experiment consisted of five treatments: no fertilizer (CK), single nitrogen (urea, N), single oilseed rape cake fertilizer (R), nitrogen + cake fertilizer (2:1, NR1), and nitrogen + cake fertilizer (1:2, NR2). The fertilization proportion of NR1 and NR2 was determined by the nitrogen content of nitrogen fertilizer and cake fertilizer. The results revealed that the single application of nitrogen had no significant effect on soil CO2 flux. However, the addition of cake fertilizer significantly increased CO2 emissions through enhanced soil microbial biomass carbon (MBC). Additionally, CO2 emissions were directly proportional to the amount of carbon (C) in the fertilizer. All treatments were minor sinks for CH4 except for the treatment NR1. Specifically, the cumulative CH4 fluxes of NR1 and NR2 were significantly higher than rest of the three treatments, which implies that application of urea and oilseed rape cake reduced the capability of CH4 oxidation in tea soil. Structural equation models indicated that soil CO2 flux is significantly and positively correlated with soil dissolved organic carbon, MBC and soil pH, while mineral nitrogen content was the main factor affecting CH4 flux. Overall, the application of oilseed rape cake increased the oxidation of CH4 and promoted soil C sequestration but inevitably increased the soil CO2 emissions.